A Critical Eco-perspective in English Textbook for Indonesian 12th Graders: A Case on Nationally Issued Textbook - Seli, Fenny Yutika; Manar, Marsandi; Hardono, Adinda Apriliani; 'Aini, Syarifah (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Ecological values in textbooks are essential because they help instill environmental awareness and responsibility in students from an early age to support sustainable development. The study addresses how ecological values are portrayed in Indonesian 12th-grade English textbooks. Using a qualitative content analysis framework, this study examines the transitivity system found in the textbook. The analysis emphasizes environmental conservation, sustainable practices, and encouraging cognitive engagement through positively framed language and relatable, contextual examples. Through a thorough exploration of how elements are connected, positive language use, and specific contextual details, the research provides nuanced insights into the representation of ecological values. This research provides valuable insights into the nuanced instructional approach that shapes environmental awareness within the context of these textbooks. These findings suggest that English Language Teaching (ELT) materials for Indonesian students should actively incorporate eco-friendly linguistic elements and emphasize sustainability-oriented pedagogy to cultivate environmental responsibility.